[Brazilian purpuric fever, virulence in an animal model of Haemophilus aegyptius (H. influenzae biogroup aegyptius). Grupo de Estudo da Febre Purpúrica Brasileira]. - M C Brandileone; Rosemeire Cobo Zanella; M. L. C. Tondella; L L Gheesling; Vera Simonsen Dias Vieira; G M Carlone (1993)
Brazilian purpuric fever (BPF) is caused by invasive strains of Haemophilus aegyptius (H. influenzae biogroup aegyptius, Hae). These strains were differentiated from Hae strains associated only with conjunctivitis (non-invasive Hae strains) through specific molecular markers. Complement-depleted infant rat model was used to study the invasive and non-invasive Hae strains to compare their virulence potential. Inoculating 10(5) bacteria in the rats, the invasive strains caused 80 to 100% bacteremia and the intensity of bacteremia was 10(2.5 +/- 0.49) to > 10(4.69) cfu/ml of blood. Using the same infectious dose, the non-invasive strains did not cause frequent bacteremia (0 to 50%) and the intensity was 0 to 10(3.69 +/- 0.53) cfu/ml of blood. The infectious doses able to cause 50% of bacteremia in the rats (BD 50%) varied from < 10(3) to 10(4.2) bacteria for the invasive strains, whereas the BD 50% were 10(6.2) to > 10(7.3) bacteria for non-invasive strains. Passive immunization using antisera to invasive strains protected rats against bacteremia caused by homologous strains, but not by heterologous strain. By comparing the bacteremia caused by Hae and bacteremia caused by H. influenzae b (Eagan strain, Hib), it was demonstrated that Hib had higher virulence potential. This animal model was useful to clarify the virulence potential of invasive Hae strains.